A Comparative Study on the Biodegradation of 17β-Estradiol by Candida utilis CU-2 and Lactobacillus casei LC-1 - Ge, Huiru; Yang, Liansheng; Li, Benhang; Feng, Yuyan; Wang, Shurui; Zheng, Yue; Feng, Li; Liu, Yongze; Du, Ziwen; Zhang, Liqiu (Frontiers in Energy Research, 2021)
The release and fate of estrogens have attracted more and more public attention. Biodegradation is an important method for estrogens removal from the environment. However, few comparative studies were concentrated on the degradation of 17β-estradiol (E2) by fungi and bacteria. In this study, the removal efficiencies of E2 by fungi (Candida utilis CU-2) and bacteria (Lactobacillus casei LC-1) were investigated through influencing factors, kinetics and biodegradation pathways. The results demonstrated that both Candida utilis CU-2 and Lactobacillus casei LC-1 could effectively degrade E2 (10 μM) with nearly 97% degradation rate. However, the biodegradation rate could only reach 20% when E2 was used as a sole carbon source while it could be up to 97% with 1.2 g/L sucrose, glucose or sodium acetate supply, indicating the occurrence of co-metabolism. In addition, the results indicated that 35℃ and 0.6 g/L sucrose favored the degradation. However, excessive carbon sucrose addition (10 g/L) would significantly inhibit the biodegradation of E2. Besides, the degradation of E2 with 0 10 g/L sucrose as co-substrate followed the first-order kinetics well. Through intermediate products analysis, twelve degradation products were identified and they were mainly produced via hydroxylation and methylation, etc, among which C14H22O4 (m/z:[M+H]+=255) was detected as the product with the smallest amount of carbon in this study. Based on the detected products and previous studies, five biodegradation pathways were proposed. To our knowledge, this is the first report to study the comparisons of E2 removal between fungi and bacteria. Moreover, the results confirmed that the strain CU-2 and strain LC-1 may have similar degradation characteristics and metabolic mechanisms in the degradation of E2. This study may provide a promising bio-treatment for E2 removal from aqueous environments and help understanding their biodegradation mechanisms.